Efficacy of speech pathology management for chronic cough: a randomised placebo controlled trial of treatment efficacy - Vertigan, A E (BMJ Group, 2006)
BACKGROUND: Chronic cough that persists despite medical treatment may respond to speech pathology intervention, but the efficacy of such treatment has not been investigated in prospective randomised trials. The aim of this study was to determine the efficacy of a speech pathology intervention programme for chronic cough. METHODS: A single blind, randomised, placebo controlled trial was conducted in 87 patients with chronic cough that persisted despite medical treatment. Patients were randomly allocated to receive either a specifically designed speech pathology intervention or a placebo intervention. Participants in both groups attended four intervention sessions with a qualified speech pathologist. RESULTS: Participants in the treatment group had a significant reduction in cough (8.9 to 4.6, p<0.001), breathing (7.9 to 4.7, p<0.001), voice (7.3 to 4.6, p<0.001) upper airway (8.9 to 5.9, p<0.001) symptom scores and limitation (2.3 to 1.6, p<0.001) ratings following intervention. There was also a significant reduction in breathing (6.8 to 5.6, p = 0.047), cough (7.6 to 6.3, p = 0.014), and limitation (2.3 to 2.0, p = 0.038) scores in the placebo group, but the degree of improvement was significantly less than in the treatment group (p<0.01). Clinical judgement of outcome indicated successful ratings in 88% of participants in the treatment group compared with 14% in the placebo group (p<0.001). CONCLUSION: Speech pathology is an effective management intervention for chronic cough which may be a viable alternative for patients who do not respond to medical treatment.